Vascularization of a bone stump - Viktor Shevchuk; Yurii Bezsmertnyi; Yankai Jiang; Olexander Branitsky; Halyna Bezsmertna; Dmytro Bondarenko (Medicinski glasnik, 2023)
Aim: To study the character of blood circulation in the bone stump at tight and loose closure of the medullary cavity. Methods: Two series of experiments on 39 rabbits with mid-third femoral amputation and muscular plasty were carried out. In the 1st (experimental) series, the bone scapula was closed by thin cortical autograft taken from the epimetaphyseal area, and then the muscles were sutured, and in the 2nd - the scapula was closed by myoplasty only. Follow-up periods: 1st series - 7, 14, 21 days and 1, 3, 6 months, 2nd series - 1, 3, 6 months. Histological methods with infusion of vessels with ink-gelatin mixture and morphometry was used. Results: In the 1st series there was a rapid restoration of the disturbed macro- and microcirculation due to the reserve sources of blood circulation and the development of extravascular ways of microcirculation. In the 2nd series, blood circulation recovery was significantly slower and occurred mainly due to the development of extravascular microcirculatory pathways. Conclusion: The study established undeniable usefulness of tight closure of the bone marrow cavity during amputation.
Keywords: amputation; bone graft; canal; microcirculation